Isolation, and Identification of Diesel Oil Degrading Bacteria in Water Contamination Site and Preliminary analysis with Potential Bacterial Gordonia terrae - Ainun Ramadhani Tri Wahyuni; Endang Yuli Herawati; Andi Kurniawan; Abd. Aziz Amin (Research Journal of Life Science, 2019)
Bioremediation is one of kind method which use of bacteria to degrade of hydrocarbon to be another compound. This study aims to get isolation of indigenous bacteria and potential test with Gordonia terrae on diesel oil bioremediation. The water sample was taken from Tanjung Perak Port of Surabaya, Indonesia where contaminated with diesel oil. Analysis of in-situ water quality parameters were consist of Dissolved oxygen, temperature, pH, salinity. Strain isolate bacteria were isolated by Bushnell-Hass medium. The bacterial density result shows in IN6 shows that bacterial density increased up to 9 × 108 cells/ml at day 2 incubation and decrease up to 1.79 × 108 cells/ml at final incubation, IN8 increased up to 8.6 × 108 cells/ml, then decrease up to 3.57 × 108 cells/ml. While, EX8 increased up to 9.1 × 108 cells/ml, and then decrease up to 3.06 × 108 cells/ml. While, results of degradation diesel oil hydrocarbon show treatment IN6, TPH values showed a decrease in the initial hydrocarbon concentration of 30 ppm to 16 ppm. IN8 TPH value shows a decrease in the initial hydrocarbon concentration of 30 ppm to 16 ppm. EX8 TPH value shows a decrease in the initial hydrocarbon concentration of 30 ppm to 24 ppm. In this experiment was found that Bacillus cereus was effectively degrading of diesel oil and can be agent bacterial for bioremediation.